2021
DOI: 10.30892/gss.1404-074
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Legacy Impacts of Mega-Event Stadia: Selected Case Studies from South Africa

Abstract: This study considered the urban infrastructure legacy impacts of mega-events in the Global South with a specific focus on South Africa’s 2010 stadia. By way of multiple case studies, undertaken in 2010 FIFA World Cup stadia in host cities Cape Town, Durban and Port Elizabeth, and applying a mixed-method approach, n=1120 urban residents living within a 2-km radius were surveyed in addition to interviews with key resource persons. The empirical findings indicate the existence of significant statistical differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…South Africa established itself as a prominent sport tourism des�na�on through its successful hos�ng of a spectrum of spor�ng events, from small-scale and recurring events to mega and one-�me occurrences, as documented in the literature (Bama and Tichaawa 2015). Notably several iconic sport tourism events have been hosted in the country over the years, including the 1995 Rugby World Cup, the 1996 African Na�ons Cup, the 2003 Cricket World Cup, the 2009 FIFA Confedera�ons Cup, the 2010 FIFA World Cup, as well as recurring events such as the Cape Town Cycle Tour, the Two Oceans Marathon, the annual Durban July, and the Comrades Marathon (Bama and Tichaawa, 2021;Knot and Hemmonsbey, 2015). These events collec�vely contribute to South Africa's status as a leading sport tourism des�na�on.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…South Africa established itself as a prominent sport tourism des�na�on through its successful hos�ng of a spectrum of spor�ng events, from small-scale and recurring events to mega and one-�me occurrences, as documented in the literature (Bama and Tichaawa 2015). Notably several iconic sport tourism events have been hosted in the country over the years, including the 1995 Rugby World Cup, the 1996 African Na�ons Cup, the 2003 Cricket World Cup, the 2009 FIFA Confedera�ons Cup, the 2010 FIFA World Cup, as well as recurring events such as the Cape Town Cycle Tour, the Two Oceans Marathon, the annual Durban July, and the Comrades Marathon (Bama and Tichaawa, 2021;Knot and Hemmonsbey, 2015). These events collec�vely contribute to South Africa's status as a leading sport tourism des�na�on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many countries around the world are ac�vely involved in the organisa�on and management of spor�ng events for the opportuni�es they present to des�na�ons. As a result, these events are being integrated into na�onal development strategies (Bama 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sport event tourism in South Africa has experienced significant growth in the last two decades, and the government has largely focused on continuously growing the sector by marketing and branding the country as a world-renowned sporting destination (Knott et al, 2015b;Nyikana, 2016;Swart et al, 2018;McKay et al, 2019;Daniels and Tichaawa, 2021). South Africa has hosted a series of major and megasporting events that have contributed towards the socio-economic development of the country (Bama and Tichaawa, 2020b). More importantly the growth of sport event tourism in South Africa has encouraged other developing countries, particularly in Sub-Saharan Africa to bid and successfully host major sporting events (Achu et al, 2015).…”
Section: Contextualising Sporting Events In the Covid-19 Eramentioning
confidence: 99%
“…Beyond the often-mentioned economic benefits that the sector brings, sport tourism is also associated with other implications such as the improvement in the wellbeing of residents, increased employment opportunities and improved infrastructure specifically transportation systems, as well as enhanced environmental awareness (Knott et al, 2015a;Bama and Tichaawa, 2020b;Mchunu et al, 2021). Some scholars (Malchrowicz-Mosko and Munsters, 2018;Zarotis, 2020) have observed that sporting events, as a sport tourism product, promote cultural diversity during their hosting.…”
Section: Introductionmentioning
confidence: 99%